2023
DOI: 10.3389/fcimb.2023.1112229
|View full text |Cite
|
Sign up to set email alerts
|

The application of metagenomic next-generation sequencing in pathogen diagnosis: a bibliometric analysis based on Web of Science

Abstract: BackgroundInfectious disease is a large burden on public health globally. Metagenomic next-generation sequencing (mNGS) has become popular as a new tool for pathogen diagnosis with numerous advantages compared to conventional methods. Recently, research on mNGS increases yearly. However, no bibliometric analysis has systematically presented the full spectrum of this research field. Therefore, we reviewed all the publications associated with this topic and performed this study to analyze the comprehensive statu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Citation analysis is a pivotal element of bibliometric studies, serving as an indicator of an article’s impact. [ 14 ] WOS is esteemed as a comprehensive research platform across various fields and is globally acknowledged as a reliable citation database by prestigious publishers. [ 15 ] Table S1, Supplemental Digital Content, http://links.lww.com/MD/M94 shows the 3 most frequently cited articles revolve around “Photodynamic Therapy,” “Immunotherapy with Anti-PD1 Antibodies,” and “Hedgehog Pathway Therapeutic Potential.” Remarkably, the 2020 article “Clinical Development and Potential of Photothermal and Photodynamic Therapies for Cancer” from Nature Reviews Clinical Oncology not only secured the highest total citation count but also the highest average annual citation rate.…”
Section: Resultsmentioning
confidence: 99%
“…Citation analysis is a pivotal element of bibliometric studies, serving as an indicator of an article’s impact. [ 14 ] WOS is esteemed as a comprehensive research platform across various fields and is globally acknowledged as a reliable citation database by prestigious publishers. [ 15 ] Table S1, Supplemental Digital Content, http://links.lww.com/MD/M94 shows the 3 most frequently cited articles revolve around “Photodynamic Therapy,” “Immunotherapy with Anti-PD1 Antibodies,” and “Hedgehog Pathway Therapeutic Potential.” Remarkably, the 2020 article “Clinical Development and Potential of Photothermal and Photodynamic Therapies for Cancer” from Nature Reviews Clinical Oncology not only secured the highest total citation count but also the highest average annual citation rate.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have shown that metagenomic next-generation sequencing (mNGS) technology exhibits key characteristics, including wide pathogen coverage, fast detection, high positive rate, unbiased detection, and effective detection of dead pathogens ( Gu et al., 2019 ; Wensel et al., 2022 ; He et al., 2023 ; Kullar et al., 2023 ). It plays a critical role in the diagnosis of infectious diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Metagenomic next generation sequencing (mNGS) is an emerging method with the potential for screening pathogens, offering the ability to significantly improve diagnostic accuracy when conventional culture methods yield negative results. 2 mNGS involves the rapid sequencing of nucleic acid sequences in samples using a second-generation sequencing platform, which are then compared with genomic sequences of individual species to identify and quantify microorganisms present. The process of detecting pathogenic microorganisms using mNGS typically involves six steps: sample collection from the patient’s infection sites, extraction of nucleic acids, construction of a standard sequencing library, high-throughput sequencing, bioanalysis to identify pathogenic bacteria, and interpretation of the results.…”
mentioning
confidence: 99%